ANALISIS ADOPSI TEKNOLOGI, AKSES PASAR DIGITAL, DAN INOVASI PRODUK TERHADAP DAYA SAING UMKM DI ERA TRANSFORMASI DIGITAL - Febriani, Febby; Nasution , Eri Yanti (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2025)
This study aims to analyze the influence of technology adoption, digital market access, and product innovation on the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the era of digital transformation. The research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. Data were collected through the distribution of questionnaires to 100 MSME actors who have adopted digital technologies. The findings reveal that only the variable of digital market access has a significant effect on MSME competitiveness, whereas technology adoption and product innovation do not demonstrate a statistically significant influence. These results highlight the critical role of optimizing digital market utilization to expand reach and enhance MSMEs’ positioning within a competitive marketplace. The study further provides strategic recommendations for MSMEs to enhance their competitiveness in a sustainable manner through strengthened digitalization and more targeted innovation efforts.